PHYSICO-CHEMICAL ANALYSIS ON CROTON TIGLIUM OIL FOR POTENTIAL USE AS BIODIESEL - V.N ARIHARAN; V.N MEENA DEVI; N.K.PARAMESWARAN; P. NAGENDRA PRASAD (International Journal of Pharma and Bio Sciences, 2015)
The increasing consumption of energy with the depletion of crude oil reserves urges the usage of alternative fuel. Since there is an existing demand for edible vegetable oils, waste vegetable oils and non-edible crude vegetable oils are preferred as potential low priced biodiesel sources. In this present work the utilization of a commonlyavailable bioenergy crop in the Western Ghats region,Croton tigliumis evaluated for its use as biodiesel by physico -chemical analytical method. The Croton tiglium is a member of Euphorbiaceae family. It is a multi-functional bioenergy crop of significant economic importance because of its several industrial and medicinal purposes.The Physico- Chemical Properties of the oil was analyzed by blending with conventional diesel at 10%(B10) and 20%(B20)proportions.The properties assessed in the physical parameters includes,pH,Density Salinity, Viscosity, Specific gravity, Conductivity, Total dissolved solid and Total dissolved oxygen. The significant biodiesel characters like flash point, fire point, smoke point, pour point, cloud point andcarbon residue were also assessed. The chemical parameters estimated such as Acid value, Iodine value and Saponification value. The values were compared with the ASTMT standards of biodiesel. The blend B20 is found to be within the ASTM standard and it can serve as a potential source for biodiesel.